Round robin test for odour testing of migration waters. (15th April 2015) - Rapp, Thomas; Günther, Herbert
Abstract: For a round robin test for EN 1420-1 (Odour assessment for organic materials in contact with drinking water) with 14 contributing laboratories from 10 European countries segments of a plastic pipe were sent to the laboratories which performed a migration test and an odour analysis of the migration waters (water that had contact with the organic material) according to the procedure described in the standard from 1999. In addition reference substances (Methyl tert -butyl ether, 1-butanol and hexanal) were investigated for their suitability to qualify the panels and the individual panellists. Methyl tert -butyl ether (MtBE) and 1-butanol proved to be suitable for this purpose, whereas hexanal showed a wide distribution of the individual odour threshold concentrations. Both possible testing options (unforced and forced choice) were performed and gave similar results. However, with respect to the qualification of the panellists and the data analysis the unforced choice procedure showed advantages. As human olfactory perception is used for the analysis, the reproducibility and the comparability between laboratories is of particular concern. For the pipe material the TON results of the different laboratories were in a range of ±1.5 dilutions based on a dilution factor of 2. This might be improved by taking the individual sensitivities of the panellists into account more strongly. Appropriate measures for the improvement of the test method appear to be the use of the proposed reference substances for the training of the panellists as well as the auditing and the selection of the panellists. The results of this round robin test are used in the revision process of the standard. Highlights: The results of a round robin test for EN 1420-1 with 14 participating laboratories are presented and discussed. The forced and unforced choice testing procedure were compared to determine Threshold Odour Numbers (TON). The unforced choice procedure showed advantages in respect to the qualification of the panelists. Methyl-tert-butyl ether and 1-butanol are suitable substances for the qualification of the panelists. The comparability of results of different qualified panels is in the range of ±1 dilution (range: 4 times the lower concentration).